NR2F6 as a Disease Driver and Candidate Therapeutic Target in Experimental Cerebral Malaria - Victoria E. Stefan; Victoria Klepsch; Nikolaus Thuille; Martina Steinlechner; Sebastian Peer; Kerstin Siegmund; Peter Lackner; Erich Schmutzhard; Karin Albrecht-Schgör; Gottfried Baier (Cells)
Cerebral malaria (CM) is the severe progression of an infection with Plasmodium falciparum, causing detrimental damage to brain tissue and is the most frequent cause of Plasmodium falciparum mortality. The critical role of brain-infiltrating CD8+ T cells in the pathophysiology of CM having been revealed, our investigation focuses on the role of NR2F6, an established immune checkpoint, as a candidate driver of CM pathology. We employed an experimental mouse model of CM based on Plasmodium berghei ANKA (PbA) infection to compare the relative susceptibility of Nr2f6-knock-out and wild-type C57BL6/N mice. As a remarkable result, Nr2f6 deficiency confers a significant survival benefit. In terms of mechanism, we detected less severe endotheliopathy and, hence, less damage to the blood–brain barrier (BBB), accompanied by decreased sequestered parasites and less cytotoxic T-lymphocytes within the brain, manifesting in a better disease outcome. We present evidence that NR2F6 deficiency renders mice more resistant to experimental cerebral malaria (ECM), confirming a causal and non-redundant role for NR2F6 in the progression of ECM disease. Consequently, pharmacological inhibitors of the NR2F6 pathway could be of use to bolster BBB integrity and protect against CM.